2002
DOI: 10.1046/j.1365-8711.2002.05669.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy groups in the 2dF Galaxy Redshift Survey: galaxy spectral type segregation in groups

Abstract: The behaviour of the relative fraction of galaxies with different spectral types in groups is analysed as a function of projected local galaxy density and the group‐centric distance. The group sample was taken from the 2dF Group Galaxy Calatogue constructed by Merchán & Zandivarez. Our group sample was constrained to have a homogeneous virial mass distribution with redshift. Galaxies belonging to this group sample were selected in order to minimize possible biases, such as preferential selection of high‐lumino… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 43 publications
10
53
1
Order By: Relevance
“…The observed morphology-density (e.g., Dressler 1980;Postman & Geller 1984;Dressler et al 1985;Goto et al 2003) and morphology-clustercentric radius (e.g., Whitmore & Gallagher 1991;Domínguez et al 2002;Goto et al 2003) relations for galaxies are in qualitative agreement with the trends obtained here for halos. The fraction of intermediate-type galaxies (mostly S0's) increases from the outskirts of clusters to intermediate cluster radii, while the fraction of late-type galaxies decreases.…”
Section: The Morphology-density Relation and Its Evolutionsupporting
confidence: 82%
See 1 more Smart Citation
“…The observed morphology-density (e.g., Dressler 1980;Postman & Geller 1984;Dressler et al 1985;Goto et al 2003) and morphology-clustercentric radius (e.g., Whitmore & Gallagher 1991;Domínguez et al 2002;Goto et al 2003) relations for galaxies are in qualitative agreement with the trends obtained here for halos. The fraction of intermediate-type galaxies (mostly S0's) increases from the outskirts of clusters to intermediate cluster radii, while the fraction of late-type galaxies decreases.…”
Section: The Morphology-density Relation and Its Evolutionsupporting
confidence: 82%
“…The main observable dependencies with environment are seen for the morphological mix of elliptical and spiral galaxies (e.g., Dressler 1980;Postman & Geller 1984;Whitmore et al 1993;Domínguez et al 2002;Goto et al 2003), color and specific star formation rate (e.g., Balogh et al 1998Balogh et al , 2004Kodama et al 2001;Tran et al 2001;Pimbblet et al 2002;Lewis et al 2002;Blanton et al 2003;Gómez et al 2003;Kauffmann et al 2004;Hogg et al 2004;Tanaka et al 2004;Croton et al 2005). Besides, there is some evidence that these dependencies evolve, becoming weaker at higher redshifts (Treu et al 2003;Goto et al 2004;Bell et al 2004;Smith et al 2005;Postman et al 2005).…”
Section: M0mentioning
confidence: 99%
“…In fact, Carlberg et al (2001b) found the presence of a color gradient only in groups with σ v > 150 km s −1 , and Domínguez et al (2002) detected spectral-type segregation only in groups with mass M ∼ > 10 13.5 h −1 M . Additional support to this idea is given by our analysis in Sect.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This result suggests that galaxy transformation starts to occur in the infalling filaments, which consist of chains of groups in which field galaxies are affected by the group environment which changes their star-forming blue field-like properties into passive, red cluster-like galaxies. But even if groups seem to be the key environment to search for the nurture scenario, still the observational evidence for related segregation phenomena is quite scarce and holds mainly for the local Universe (Postman & Geller 1984;Mahdavi et al 1999;Tran et al 2001;Carlberg et al 2001a,b;Girardi et al 2003;Domínguez et al 2002;Wilman et al 2009;Bai et al 2010;Ribeiro et al 2010).…”
Section: Introductionmentioning
confidence: 99%